Analisis Pengaruh Kualitas Situs Web Toko Online Shopee Terhadap Niat Pembelian Online - Angela Triwani Stefani Sitorus; Mariana Simanjuntak (BADAN PENERBIT STIEPARI PRESS, 2024)
Abstract This research analyzes the influence of the quality of the online shop website Shopee on consumers' online purchasing intentions. Using a quantitative approach, this study investigates four dimensions of website quality: information quality, ease of use, website design, and trustworthiness. Data was collected through an online survey of active Shopee users using a questionnaire with a Likert scale. Online purchase intention is measured based on the possibility of buying, desire to buy, and intention to seek information. Statistical analysis was used to determine the relationship between website quality and purchase intention, as well as identify the most influential dimensions. It is hoped that the results of this research will provide insight into developing marketing strategies and improving the performance of online shop websites, especially Shopee, in increasing consumers' online purchasing intentions.